Characterization of Material Damage by Ultrasonic Immersion Test. (2015) - Castellano, Anna; Foti, Pilade; Fraddosio, Aguinaldo; Galietti, Umberto; Marzano, Salvatore; Piccioni, Mario Daniele
Abstract: We present an innovative non-destructive experimental technique for a quantitative determination of the damage level in structural components. In particular, we study the propagation of ultrasonic waves in an isotropic material specimen before and after a mechanical fatigue incremental test. To this aim, we use an innovative goniometric device for ultrasonic immersion tests, designed and built for the mechanical characterization of anisotropic materials. In the first test, performed in absence of damage, we characterize the mechanical behavior of the isotropic material by the measure of time of flight (TOF) of ultrasonic waves, and then by determining the so-called natural velocities. In the next ultrasonic tests, performed after each fatigue test, we determine the response of the damaged material by measuring again the velocity of ultrasonic waves: the comparison between these velocities and the natural velocities allows for the evaluation of the level of damage in the material. Moreover, through the goniometric ultrasonic immersion device it is possible to relate the damage to the stress-induced anisotropyacquired by the specimen, which we characterize by identifying the acoustic axes and the dependence of the velocity of the ultrasonic waves on the direction of propagation.